The Literary Comparisons In Classical Arabic Literature - İbrahim Şaban (Darulfunun Ilahiyat)
“Comparative literature” that started with Villemain and Ampère in the first quarter of the 19th century began to spread in the academic circles of Arab countries after the Second World War. However, comparisons were made between literary works in Arabic before modern comparative literature. Although most of these comparisons occur between products in the same language, there are also comparisons between products in different languages. Until the modern period, terms such as “mufâdala,” “tabaqat,” “muvâzana,” “vasâta,” “comparison,” “musâvât,” “mukâbele,” and “mukarane” were used for literary product comparisons. While “mufadala” was used for works that included comparisons of literary products generally in the same language and rarely in different languages in the Jahiliyya, Sadru’l-Islam, and Umayyad Periods, “tabaqat,” “muvâzana,” and “vasâta” were used for works in the Abbasid Period. The term “mukâbala” was used to refer to product comparisons in different languages in the 19th century, and “mukarane” was generally used for works in the 20th century. This study aimed to deal with the first literary product comparisons in classical Arabic literature in the form of “mufâdale,” “tabaqat,” “muvâzene,” and “vasâta” as an introduction. For this aim, this study will attempt to answer the questions of when the first literary comparisons in Arabic literature began, how they developed, whether they were compared with literary products in different languages, and what was considered in the comparisons.